Comparison of two three-phase pll systems for more electric aircraft - Bifaretti, Stefano; Zanchetta, Pericle; Lavopa, Elisabetta (IEEE, 2014)
The More Electric Aircraft power system is characterized by variable supply frequency, in general between 360Hz and 900Hz. All equipment on board the aircraft have to operate delivering high performance under this variable frequency condition. In particular, power electronic converters need accurate control algorithms able to track the fundamental phase and frequency in real time, both in normal and unusual conditions. Phase Locked Loop (PLL) based algorithms are commonly used in traditional single and three phase power systems to provide phase and frequency estimations of the supply. Despite the simplicity of those algorithms, large estimation errors can arise when power supply voltage has variable frequency or amplitude, presents unbalances or is polluted with harmonics. To improve the quality of the phase and frequency real-time estimations, a robust PLL algorithm, based on a prediction-correction filter, is presented in this paper and compared with a Discrete Fourier Transform (DFT) based procedure. The performances of the two algorithms, implemented in a floating-point DSP, have been compared through an experimental validation obtained on a laboratory power converter prototype.